Tourism Development in UNESCO Natural Heritage Sites: The Case of Sicilian Volcanic Sites: Mount Etna and Aeolian Islands - Ruggieri, Giovanni; Calderón-Vázquez, Francisco José (David Publishing Company (Chinese Business Review), 2017)
Local development often depends on tourism, especially in fragile contexts like islands which represent a special cluster and are the best cases to be analyzed in order to highlight positive and negative aspects of economic development driven by tourism. A sustainable development approach should be taken in account and the UNESCO brand plays a fundamental role in this sense. The aim of this paper is to analyze the link between tourism supply and the growth of tourism demand in the case of UNESCO sites through multivariate regression analysis. The results show a correlation between the variables considered. But the actual structure of supply is still built on conventional sea tourism and is not yet organized to host and attract tourism demand connected with the UNESCO active volcano area. The UNESCO brand could guarantee a new approach for local tourism development if associated with a specific tourism supply structure.
Keywords: Patrimonio; Biología de la conservación; Volcanes - Sicilia; Development; Islands; Tourism; Sustainability; Analysis